Comparative analysis of incidence of dentinal defect with different taper of rotary instrument use stereomicroscope (Mustansiria Dental Journal, 2024)
Aims: Study the effect of canal preparation with different Niti rotary system (Edge x7 file and F-one file) with different taper (0.04 and 0.06) on the incidence of dentinal defect. Methods and Material: 75 straight palatal root  of maxillary first molar were collected, the instrumentation was done to 11 mm root length for all sample except control group, the sample were divided randomly into five group (n=15), Group (A) was a control, Group (B) with Edge x7 taper (0.04), Group (C) with Edge x7 taper (0.06), Group (D) with F-ONE taper (0.04), and Group (E) with  F-ONE taper (0.06)  Every sample had a horizontal section from the apex at  2 mm, 4.5 mm, and 7 mm, dentinal defect was evaluated with 25x stereomicroscope. Statistical analysis used: The data were statistically evaluated at significance levels of 5% or more using Fisher's exact test. Results: Ther is no significant difference between different taper and between different file, in general taper 0.04 showed less dentinal defect than taper 0.06, and Edge x7 showed less defect than F-ONE. Conclusions: Dentinal defects were present in all experimental groups, but not in control group.